Information System for the Improvement of Telecommunication Service Quality - Assis, Elvis; Tavares, Emmanuel; Rodríguez, Demóstenes; Rosa, Renata (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2017)
This work describes an information system regarding to the telecommunication service with the goal to inform to the telephony service users about the operators signal quality and the users’ opinion about the telecommunication operators. The system contains information of cellular base station locations and the results are crossed with sentiment analyses of sentences extracted from a social network, which are related to the telecommunication services. The study aims to detect complaints and dissatisfaction of users about a determined service, helping to make a relation between the users’ complains extracted from social network with the number of base stations in the same geographic area of the user's social network. Therefore, the proposed information system can be used by the National Telecommunications Agency of each country for monitoring the quality-of-service of cellular network operators.